+0  
 
0
258
1
avatar

3x(-2)

Guest Jul 1, 2017
 #1
avatar+92917 
+1

3x(-2)

 

depends what you mean...

 

\(3\times (-2)=-6\\ 3x\times (-2)=-6x\\ 3x^{-2}=\frac{3}{x^2}\\ (3x)^{-2}=\frac{1}{9x^2} \)

Melody  Jul 2, 2017

11 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.